High-strength poly (siloxane-imide) high-temperature thermoplastic elastomer and preparation method thereof
The poly(siloxane-imide) thermoplastic elastomer is solved by reacting and imidizing the reaction of aminohydrocarbon-terminated polysiloxane with aromatic dianhydride and carboxydiamine-containing crosslinking with metals at high temperatures. The problem of poor mechanical properties has achieved the preparation of poly(siloxane-imide) thermoplastic elastomers with high tensile strength, elongation of break and high thermoplastic temperature, meeting the special requirements for high temperature applications.
Patent Information
- Application Number
- CN202411478420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-27
AI Technical Summary
The existing poly(siloxane-imide) thermoplastic elastomers have poor mechanical properties at high temperatures, low tensile strength, small elongation at break, and insufficient thermoplastic temperature, making it difficult to meet the special requirements in high temperature applications.
The anhydride-terminated polysiloxane and aromatic diacid anhydride are synthesized with anhydride-terminated poly(siloxane-amic acid) prepolymer, and chain-extended reaction with the carboxyl-containing substituted aromatic diamine, followed by imine The mixture is coordinated and crosslinked to form a high-strength poly(siloxane-imide) thermoplastic elastomer.
The tensile strength, elongation of break and thermoplastic temperature of the material are significantly improved, ensuring good mechanical properties and temperature resistance at high temperatures, meeting the needs of high temperature applications.
Smart Images

Figure BDA0005096698330000031 
Figure BDA0005096698330000051 
Figure BDA0005096698330000052
Abstract
Description
Technical Field
[0001] The invention relates to a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer and a preparation method thereof, belonging to the technical field of synthesis of organic silicon polymer materials. Background Art
[0002] Thermoplastic elastomers are a type of elastomer that has the elasticity of rubber at room temperature and can be plasticized at high temperatures. They are usually crystalline or have a high glass transition temperature (T g ) hard segment and a soft segment with high elasticity. At room temperature, the hard segment forms a physical cross-linking network through the interaction between the chain segments, which plays the role of physical cross-linking and reinforcing filler, while the molecular chain of the soft segment gives the material high elasticity. Linear polysiloxane has excellent properties such as high and low temperature resistance, aging resistance, weather resistance, hydrophobicity, flame retardancy and physiological inertness, and is an ideal soft segment polymer. Polyimide has excellent high temperature resistance, flame retardancy and dimensional stability due to the aromatic ring and cyclic imide structure in its molecular structure. Poly(siloxane-imide) with polysiloxane as the soft segment and polyimide as the hard segment can combine the advantages of the two polymers and is an ideal thermoplastic elastomer material.
[0003] In view of the special requirements of some high-temperature application fields, it is necessary to develop poly(siloxane-imide) thermoplastic elastomers that have both excellent mechanical properties and high operating temperatures. This requires that the material can maintain good dimensional stability at higher operating temperatures, that is, it has a high plasticizing temperature. Since the non-polar silicone polymer and the highly polar polyimide have poor compatibility, the reaction between the two is very likely to result in sharp phase separation. It is difficult to obtain a polysiloxane-polyimide thermoplastic elastomer with ideal comprehensive performance simply by relying on the interaction between polyimide molecular chains. Chinese patent document CN111154107A discloses a polysiloxane-polyimide thermoplastic elastomer, in which double-terminated amino polysiloxane, 3,3',4,4'-biphenyltetracarboxylic dianhydride and a chain extender are dissolved and mixed by a polar solvent, reacted at room temperature, and a colorless and transparent linear polysiloxane-polyamic acid block copolymer is obtained, which is then imidized at high temperature and cold pressed to obtain a thermoplastic elastomer. However, the tensile strength of the material obtained by this method is less than 5.5 MPa, the elongation at break is less than 105%, and the mechanical properties are not ideal. Mohamed Krea et al., Polymer International 62 (2013): 1413-1424 [J] reported that amino-terminated polydimethylsiloxane was mixed with a fluorinated aromatic compound containing anhydride and amine functionalization by solution imidization, and then a poly (siloxane-imide) membrane material similar to an organophilic membrane and a gas permeation membrane was synthesized by solution imidization, but the tensile strength of the obtained material was ≤ 8.0 MPa. Xingzhong Fang et al., Journal of Applied Polymer 129 (2013): 3718-3727 [J] reported the synthesis of a series of linear poly (imide-siloxane) thermoplastic elastomers by reacting thioether-bridged aromatic dianhydrides, ether-bridged aromatic diamines and amino-terminated polydimethylsiloxane. The highest tensile strength of these elastomers reached 33.3 MPa and the elongation at break was 124%. However, their elasticity was still not ideal and their thermoplasticity was not explored.
[0004] Utilizing chemical covalent bonds to crosslink linear poly (siloxane-imide) molecules can improve the heat resistance of materials to a certain extent. Chinese patent literature CN109679495A, CN109517172A and CN114685790A disclose that linear polysiloxane is introduced into polyimide molecules, and then epoxy resin, isocyanate, acrylate, etc. are used as chemical crosslinking agents to chemically crosslink linear polyamic acid. Although such chemical covalent bond crosslinking can improve the heat resistance of materials to a certain extent, the crosslinked material loses the hot processing properties and does not belong to the category of thermoplastic elastomers. Chinese patent literature CN101469063A discloses a kind of organosilicon polyimide-polyurea elastomer, amino-terminated linear polysiloxane is mixed with pyromellitic anhydride, diisocyanate and alkoxysilane are added subsequently, imidization and chemical crosslinking are completed at high temperature to obtain elastomer. However, the patent does not disclose the tensile strength of the material, and the material is covalently cross-linked and has no thermoplasticity. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art and avoid the defects of the traditional linear poly(siloxane-imide) thermoplastic elastomer such as low strength, poor elasticity, and low thermoplastic temperature, the present invention provides a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer and a preparation method thereof. The present invention uses aminoalkyl-terminated polysiloxane and aromatic dianhydride to first synthesize anhydride-terminated poly(siloxane-amic acid) prepolymer, and then carries out a chain extension reaction with a carboxyl-substituted aromatic diamine to synthesize poly(siloxane-amic acid), and then carries out imidization, and finally metal coordination cross-linking is carried out through the carboxyl groups between the chain segments to improve the mechanical properties and thermoplastic temperature of the material to obtain a poly(siloxane-imide) thermoplastic elastomer. The poly(siloxane-imide) thermoplastic elastomer obtained by the present invention has high tensile strength, good elasticity, excellent mechanical properties, high thermoplastic temperature, and excellent temperature resistance.
[0006] The technical solution of the present invention is as follows:
[0007] A high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer, the general structure of which is as follows:
[0008]
[0009] Wherein: m, x, s, h, n are all integers greater than or equal to 1;
[0010] Ar 1 and Ar 2 are independently selected from C 6-16 Aromatic hydrocarbon groups or C containing S, N, O, F or Cl heteroatoms 6-16 Aromatic hydrocarbon groups;
[0011] R 1 , R 2 , R 3 , R 4 R is independently selected from hydrogen, a straight-chain hydrocarbon group, a branched alkyl group or a cyclic alkyl group having 1 to 18 carbon atoms and containing S, N, O or F heteroatoms or not containing the above heteroatoms, a linear or branched unsaturated hydrocarbon group having 2 to 10 carbon atoms and containing one or more unsaturated double bonds and containing S, N, O or F heteroatoms or not containing the above heteroatoms, and an aromatic hydrocarbon group having 6 to 12 carbon atoms and containing S, N, O or F heteroatoms or not containing the above heteroatoms; 1 , R 2 , R 3 , R 4 the same or different between them;
[0012] M is a metal ion.
[0013] According to the preferred embodiment of the present invention, in formula (I), Ar 1 and Ar 2 are independently selected from R 1 , R 2 , R 3 , R 4 are independently selected from hydrogen, methyl, ethyl, propyl, trifluoropropyl, ethyl nitrile, phenyl, vinyl, mercaptomethyl, mercaptopropyl; M is selected from Zn 2+ , Fe 3+ , Cu 2+ 、Co 2+ Sn 2+ or Pb 2+ .
[0014] Preferably according to the present invention, in formula (I), 1≤x≤200, 1≤s≤20.
[0015] Preferably according to the present invention, the thermoplastic temperature of the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer is 120-155° C., the tensile strength is ≥35 MPa, and the elongation at break is ≥150%.
[0016] The method for preparing the above-mentioned high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer comprises the steps of:
[0017] (1) in a solvent, an aromatic dianhydride and an aminoalkyl-terminated polysiloxane are reacted to obtain a poly(siloxane-amic acid) prepolymer solution;
[0018] (2) adding a carboxyl-substituted aromatic diamine to a poly(siloxane-amic acid) prepolymer solution to obtain a poly(siloxane-amic acid) solution through reaction; adding a catalyst to carry out imidization reaction, and then precipitating and drying to obtain a solid polymer poly(siloxane-imide);
[0019] (3) The solid polymer poly(siloxane-imide) is dissolved in an organic solvent, a metal salt is added, reacted, and then the solvent is removed to obtain a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer.
[0020] Preferably according to the present invention, in step (1), the solvent is a mixed solvent of solvent A and solvent B, wherein the volume ratio of solvent A to solvent B is (1-5):(1-5).
[0021] Preferably, solvent A is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, methyl isobutyl ketone, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, dioxane, xylene or isopropanol; solvent B is selected from tetrahydrofuran, toluene, chloroform, dichloromethane, petroleum ether, n-hexane or ethyl acetate.
[0022] According to the preferred embodiment of the present invention, in step (1), the aromatic dianhydride is selected from C 10-20 Aromatic dianhydrides or C containing S, N, O, F or Cl heteroatoms 10-20 Aromatic dianhydride; preferably, the aromatic dianhydride is selected from hexafluoroisopropylphthalic anhydride, 4,4'-oxydiphthalic anhydride or 3,3',4,4'-benzophenonetetracarboxylic dianhydride.
[0023] According to the preferred embodiment of the present invention, in step (1), the aminoalkyl-terminated polysiloxane is selected from bis(3-aminopropyl)-terminated polydimethylsiloxane, bisaminopropyl poly(methylethyl)siloxane, bisaminopropyl poly(methyltrifluoropropyl)siloxane, bisaminopropyl poly(methylphenyl)siloxane, bisaminoethyl polydimethylsiloxane, bisaminoethyl poly(methylethyl)siloxane, biscyclohexylaminopropyl polydimethylsiloxane, bisaminophenylpropyl polydimethylsiloxane, bisaminoethyl poly(methyltrifluoropropyl)siloxane or bisaminoethyl poly(methylphenyl)siloxane. Preferably, the weight average molecular weight of the aminoalkyl-terminated polysiloxane is in the range of 162 to 16000 g / mol, preferably 400 to 1100 g / mol.
[0024] Preferably, according to the present invention, in step (1), the volume ratio of the total mass of the aromatic dianhydride and the aminoalkyl-terminated polysiloxane to the solvent is 50 to 200 g / L.
[0025] Preferably, according to the present invention, in step (1), the molar ratio of the aromatic dianhydride to the aminoalkyl-terminated polysiloxane is (1-4):1.
[0026] According to the preferred embodiment of the present invention, in step (1), the reaction temperature is 0-80°C, the reaction time is 1-24h, and the reaction is carried out under stirring and inert gas protection. Preferably, the reaction temperature is 20-30°C, the reaction time is 6-10h, and the inert gas is nitrogen or argon.
[0027] Preferably, in step (1) of the present invention, the method for preparing the poly(siloxane-amic acid) prepolymer solution comprises the steps of: dissolving an aromatic dianhydride in a solvent A, adding dropwise a mixture of an aminoalkyl-terminated polysiloxane and a solvent B under stirring, and after the addition is complete, reacting to obtain a poly(siloxane-amic acid) prepolymer solution.
[0028] According to the present invention, in step (1), the poly(siloxane-amic acid) prepolymer has the structure shown below:
[0029]
[0030] Wherein, m and x are both integers greater than or equal to 1; Ar 1 , R 1 , R 2 , R 3 , R 4 The meaning is the same as in formula (I).
[0031] According to the preferred embodiment of the present invention, in step (2), the carboxyl-substituted aromatic diamine is selected from C 7-17 A carboxyl-substituted aromatic diamine; preferably, the carboxyl-substituted aromatic diamine is selected from 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, 2,4-diaminobenzoic acid, 2,6-diaminobenzoic acid or 5,5'-methylenediaminobenzoic acid.
[0032] Preferably, according to the present invention, in step (2), the carboxyl-substituted aromatic diamine is added to the reaction system in 2 to 3 times; the interval between each addition is 10 to 20 minutes.
[0033] Preferably, according to the present invention, in step (2), the molar ratio of the carboxyl-substituted aromatic diamine to the aromatic dianhydride in step (1) is 1-1.1:1.
[0034] According to the preferred embodiment of the present invention, in step (2), the reaction temperature is 0-80°C, the reaction time is 1-24h, and the reaction is carried out under stirring and inert gas protection. Preferably, the reaction temperature is 20-30°C, the reaction time is 6-10h, and the inert gas is nitrogen or argon.
[0035] According to the present invention, in step (2), the poly(siloxane-amic acid) has the general formula shown below:
[0036]
[0037] Wherein, m, x, s, and h are all integers greater than or equal to 1; Ar 1 ,Ar 2 , R 1 , R 2 , R 3 , R 4 The meaning is the same as in formula (I).
[0038] Preferably, according to the present invention, in step (2), the catalyst is selected from organic amines, organic phosphines, pyridines, benzopyridines, amidines or organic guanidine compounds; preferably, the catalyst is selected from one or a combination of two or more of triethylamine, hexamethylenetetramine, pyridine or isoquinoline.
[0039] Preferably according to the present invention, in step (2), the molar ratio of the catalyst to the carboxyl-substituted aromatic diamine is 1:(1-2).
[0040] Preferably, in step (2), the imidization reaction temperature is 60-200°C, the imidization reaction time is 1-24h, and the imidization reaction is carried out under stirring conditions and inert gas protection. Preferably, the imidization reaction temperature is 170-190°C, the imidization reaction time is 6-10h, and the inert gas is nitrogen or argon.
[0041] Preferably, according to the present invention, in step (2), the precipitation is carried out using a mixed solution of anhydrous methanol and water, wherein the volume ratio of anhydrous methanol to water is 1:1.
[0042] According to the present invention, in step (2), the solid polymer poly(siloxane-imide) has the general formula shown below:
[0043]
[0044] Wherein, m, x, s, and h are integers greater than or equal to 1; Ar 1 ,Ar 2 , R 1 , R 2 , R 3 , R 4 The meaning is the same as in formula (I).
[0045] Preferably, in step (3), the organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethyl acetate, isopropanol, toluene, chloroform, dichloromethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dioxane or xylene.
[0046] Preferably, according to the present invention, the volume ratio of the molar amount of the carboxyl-substituted aromatic diamine in step (2) to the organic solvent in step (3) is 0.1-1 mol / L.
[0047] According to the preferred embodiment of the present invention, in step (3), the metal salt is selected from one or a combination of two or more of metal halides, metal nitrates, metal sulfates or organic metal salts; preferably, the metal salt is selected from ferric acetylacetonate, zinc acetate, cobalt chloride, copper sulfate, lead nitrate, zinc chloride or stannous isooctanoate.
[0048] Preferably, according to the present invention, in step (3), the molar ratio of the metal salt to the carboxyl-substituted aromatic diamine in step (2) is 1:7-20.
[0049] Preferably, according to the present invention, in step (3), the reaction temperature is 20 to 50° C., the reaction time is 1 to 3 hours, and the reaction is carried out under stirring conditions.
[0050] The technical features and beneficial effects of the present invention are as follows:
[0051] (1) The present invention adopts a method of prepolymerization followed by chain extension, wherein precisely measured amounts of aminoalkyl-terminated polysiloxane and aromatic dianhydride are mixed and reacted to synthesize anhydride-terminated poly(siloxane-amic acid), which can effectively improve the sharp phase separation caused by poor interfacial compatibility between polysiloxane and polyimide, thereby ensuring good molecular weight and structural distribution uniformity of the final polymer elastomer and improving material stability.
[0052] (2) The crosslinking method of the thermoplastic elastomer of the present invention is the combined effect of physical crosslinking of polyimide segments and coordination crosslinking. The introduction of coordination crosslinking can make the stress dispersion between molecular chains or in molecular chains more uniform, while strengthening the crosslinking network, so that the finally obtained thermoplastic elastomer has higher strength and thermoplastic temperature.
[0053] (3) The poly(siloxane-imide) thermoplastic elastomer prepared by the method of the present invention has a tensile strength of ≥30 MPa, high tensile strength; an elongation at break of ≥150%, good elasticity; a thermoplastic temperature of higher than 120°C, and excellent heat resistance. The poly(siloxane-imide) thermoplastic elastomer of the present invention has excellent comprehensive performance, can ensure sufficient mechanical properties at higher working temperatures, and meet the use requirements under special conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is the infrared spectrum of the product obtained in Example 1 of the present invention.
[0055] Figure 2 This is a thermoplastic temperature test chart of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.
[0058] Test description:
[0059] The infrared spectrum test was carried out by Bruker Tensor 27 infrared spectrometer. The sample was pressed into potassium bromide tablets and sampled 16 times. The frequency collection range was from 4000 cm -1 Up to 400cm -1 , resolution 4cm -1 .
[0060] The mechanical properties test of the samples was conducted on an Instron 3343 material testing system. According to GB / T 1040-2006, the thin slices obtained by hot pressing the solid samples at 180℃ and 15MPa for 15min were cut into dumbbell-shaped specimens, and the mechanical properties of the materials were determined by stress-strain analysis, and at least three parallel tests were performed.
[0061] The thermoplastic temperature test of the sample was conducted by static thermomechanical analysis (TMA) using the Netzsch TMA4000. The sample was cut into strips (20×10×0.5mm), a stress of 1N was applied, the test temperature was 35℃~160℃, and the heating rate was 3℃ / min.
[0062] All tests were conducted at normal temperature, normal pressure and a relative humidity of 50%, unless otherwise stated.
[0063] Example 1
[0064] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer comprises the steps of:
[0065] (1) In an argon environment, 1332.72 mg (0.003 mol) of hexafluoroisopropylphthalic anhydride (6FDA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was completed, the reaction was stirred at 25° C. for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0066] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the poly(siloxane-amic acid) prepolymer solution in three times (about 150 mg was added each time, and the interval between each addition was 10 min). After the addition, the reaction was continued at 25°C for 8 h to obtain a poly(siloxane-amic acid) solution; 235 microliters (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185°C, and the reaction was stirred for 8 h under argon atmosphere. Finally, the polymer solution was added to a mixed solution of anhydrous methanol and water in a volume ratio of 1:1 for precipitation, and the precipitate was collected and vacuum dried at 120°C for 12 h to obtain a powder product solid polymer poly(siloxane-imide).
[0067] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran and add ZnCl 2 20.46 mg (0.00015 mol), stirred at 25 ° C for 3 hours, the reaction solution was concentrated and poured into a mold. After the solvent was evaporated, it was vacuum dried at 80 ° C for 2 hours to obtain a coordinated cross-linked poly (siloxane-imide) thermoplastic elastomer, which can be repeatedly dissolved and hot-pressed.
[0068] The obtained thermoplastic poly(siloxane-imide) was tested by Fourier transform infrared spectroscopy, and the results were as follows: Figure 1 As shown. It can be seen that at 1782cm -1 and 1724cm -1 A pair of asymmetric and symmetric stretching vibration peaks of C=O on the imide ring appeared at 1384 cm -1 The CNC stretching vibration peak on the imide ring appears at 721 cm -1 The bending vibration peak of the imide ring appeared at 1093cm -1 、1024cm -1 The Si-O-Si stretching vibration peak at 802 cm -1 Si-C bending vibration peak at 1502cm -1Stretching vibration of benzene ring at 1142cm -1 The presence of the CF characteristic peak at , proves that a poly(siloxane-imide) thermoplastic elastomer is formed.
[0069] The mechanical properties of the elastomer obtained in Example 1 were measured, and the results showed that the tensile strength was 35 MPa and the elongation at break was 246%.
[0070] The thermoplastic temperature of the elastomer obtained in Example 1 was measured, and the results were as follows: Figure 2 As shown. Figure 2 According to the analysis, the thermoplastic temperature of the thermoplastic poly(siloxane-imide) is 126.7°C.
[0071] Example 2
[0072] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer comprises the steps of:
[0073] (1) In an argon environment, 1332.72 mg (0.003 mol) of hexafluoroisopropylphthalic anhydride (6FDA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 753.75 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=500 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was completed, the reaction was stirred at 25° C. for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0074] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the poly(siloxane-amic acid) prepolymer solution in three times (about 150 mg was added each time, and the interval between each addition was 10 min). After the addition, the reaction was continued at 25°C for 8 h to obtain a poly(siloxane-amic acid) solution; 235 microliters (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185°C, and the reaction was stirred for 8 h under argon atmosphere. Finally, the polymer solution was added to a mixed solution of anhydrous methanol and water in a volume ratio of 1:1 for precipitation, and the precipitate was collected and vacuum dried at 120°C for 12 h to obtain a powder product solid polymer poly(siloxane-imide).
[0075] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran and add ZnCl 220.46 mg (0.00015 mol), stirred at 25 ° C for 3 hours, the reaction solution was concentrated and poured into a mold. After the solvent was evaporated, it was vacuum dried at 80 ° C for 2 hours to obtain a coordinated cross-linked poly (siloxane-imide) thermoplastic elastomer, which can be repeatedly dissolved and hot-pressed.
[0076] The elastomeric material has the following properties: the tensile strength of the material is 52 MPa, the elongation at break is 153%, and the thermoplastic temperature is 130.2°C.
[0077] Example 3
[0078] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer, as described in Example 1, except that in step (3), ZnCl 2 The dosage is 51.14 mg (0.00038 mol); the other steps and conditions are the same as in Example 1.
[0079] The elastomeric material has the following properties: the tensile strength of the material is 42 MPa, the elongation at break is 203%, and the thermoplastic temperature is 128.7°C.
[0080] Example 4
[0081] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer comprises the steps of:
[0082] (1) In an argon environment, 930.23 mg (0.003 mol) of 4,4'-oxydiphthalic anhydride (ODPA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was completed, the reaction was stirred at 25° C. for 8 hours to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0083] (2) Under argon atmosphere and stirring conditions, 456.45 mg (0.003 mol) of 3,5-diaminobenzoic acid was added to the poly(siloxane-amic acid) prepolymer solution in three times (about 150 mg was added each time, and the interval between each addition was 10 min). After the addition, the reaction was continued at 25°C for 8 h to obtain a poly(siloxane-amic acid) solution; 235 microliters (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185°C, and the reaction was stirred for 8 h under argon atmosphere. Finally, the polymer solution was added to a mixed solution of anhydrous methanol and water in a volume ratio of 1:1 for precipitation, and the precipitate was collected and vacuum dried at 120°C for 12 h to obtain a powder product solid polymer poly(siloxane-imide).
[0084] (3) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran and add ZnCl 2 20.46 mg (0.00015 mol), stirred at 25 ° C for 3 hours, the reaction solution was concentrated and poured into a mold. After the solvent was evaporated, it was vacuum dried at 80 ° C for 2 hours to obtain a coordinated cross-linked poly (siloxane-imide) thermoplastic elastomer, which can be repeatedly dissolved and hot-pressed.
[0085] The elastomeric material has the following properties: the tensile strength of the material is 39 MPa, the elongation at break is 265%, and the thermoplastic temperature is 124.7°C.
[0086] Comparative Example 1
[0087] A method for preparing a poly(siloxane-imide) thermoplastic elastomer comprises the steps of:
[0088] (1) In an argon environment, 1332.72 mg (0.003 mol) of hexafluoroisopropylphthalic anhydride (6FDA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was completed, the reaction was stirred at 25° C. for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0089] (2) Under the condition of argon gas and stirring, 600.72 mg (0.003 mol) of 4,4'-diaminodiphenyl ether was added to the poly(siloxane-amic acid) prepolymer solution in 5 times (about 120 mg was added each time, and the interval between each addition was 10 min). After the addition, the reaction was continued at 25°C for 8 hours to obtain a poly(siloxane-amic acid) solution; 235 microliters (0.002 mol) of isoquinoline was added to the reaction solution and the reaction was heated to 185°C, and the reaction was stirred for 8 hours under argon gas. Finally, the polymer solution was added to a mixed solution of anhydrous methanol and water in a volume ratio of 1:1 for precipitation, and the precipitate was collected and vacuum dried at 120°C for 12 hours to obtain a powder product solid polymer poly(siloxane-imide).
[0090] (3) The dried solid polymer poly(siloxane-imide) powder is dissolved in 15 ml of tetrahydrofuran, the reaction solution is concentrated and poured into a mold, and after the solvent is evaporated, it is vacuum dried at 80° C. for 2 h to obtain an uncoordinated cross-linked poly(siloxane-imide) thermoplastic elastomer.
[0091] The elastomeric material has the following characteristics: the tensile strength of the material is 23 MPa, the elongation at break is 280%, and the thermoplastic temperature is about 112.9°C.
[0092] The difference between this comparative example and Example 1 is that carboxyl-free phenylenediamine is used instead of 3,5-diaminobenzoic acid as a chain extender, and ion coordination crosslinking is not introduced, so the strength and thermoplastic temperature of the obtained material are significantly reduced.
[0093] Comparative Example 2
[0094] A method for preparing a high-strength poly(siloxane-imide) thermosetting elastomer comprises the steps of:
[0095] (1) In an argon environment, 1332.72 mg (0.003 mol) of hexafluoroisopropylphthalic anhydride (6FDA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise to the above reaction solution through a dropping funnel. After the addition was completed, the reaction was stirred at 25° C. for 8 h to prepare an anhydride-terminated poly(siloxane-amic acid) prepolymer solution.
[0096] (2) Under argon atmosphere and stirring conditions, 600.72 mg (0.003 mol) of 4,4'-diaminodiphenyl ether was added to the poly(siloxane-amic acid) prepolymer solution in 5 portions (about 120 mg was added each time, and the interval between each addition was 10 min). After the addition was completed, the reaction was continued with stirring at 25° C. for 8 h to obtain a poly(siloxane-amic acid) solution; the poly(siloxane-amic acid) solution was precipitated in a large amount of water to obtain a large amount of white flocculent precipitate, which was then vacuum dried at 80° C. for 2 h to obtain a flocculent product.
[0097] (3) The dried flocculent product was dissolved in 15 ml of N-methylpyrrolidone and imidized according to a programmed temperature increase: 80°C for 8 h, 120°C, 150°C, 200°C, and 250°C for 1 h each, to obtain a poly(siloxane-imide) thermosetting elastomer that is substantially completely insoluble and infusible.
[0098] The elastomeric material has the following characteristics: the tensile strength of the material is 32 MPa, and the elongation at break is 123%. Since it is a thermosetting material, it has no thermoplastic temperature.
[0099] The difference between this comparative example and Example 1 is that phenylenediamine without carboxyl group is used instead of 3,5-diaminobenzoic acid as chain extender, ion coordination crosslinking is not introduced, and imidization is carried out by solid-state heating. The material finally forms a covalent crosslinking network, and although there is no obvious loss in tensile strength, the elasticity is reduced and the thermoplasticity is lost.
[0100] Comparative Example 3
[0101] A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer comprises the steps of:
[0102] (1) In an argon atmosphere, 1332.72 mg (0.003 mol) of hexafluoroisopropylphthalic anhydride (6FDA) was added to a three-necked flask with a stirring device, and 18 ml of N-methylpyrrolidone was added and stirred to dissolve. Under stirring conditions, 1538.26 mg (0.0015 mol) of bis(3-aminopropyl)-terminated polydimethylsiloxane (Mw=1030 g / mol) dissolved in 9 ml of tetrahydrofuran was added dropwise through a dropping funnel. Add to the above reaction solution, after the addition is complete, add 456.45mg (0.003mol) 3,5-diaminobenzoic acid to the reaction system in 3 times (about 150mg each time, and the interval time between each addition is 10min), stir and react at 25℃ for 8h after the addition is complete, and obtain a poly(siloxane-amide acid) solution; then add 235 microliters (0.002mol) of isoquinoline to the reaction solution and heat the reaction to 185℃, and stir and react for 8h under argon. Finally, add the polymer solution to a mixed solution of anhydrous methanol and water in a volume ratio of 1:1 for precipitation, collect the precipitate, and vacuum dry at 120℃ for 12h to obtain a powder product solid polymer poly(siloxane-amide).
[0103] (2) Dissolve the dried solid polymer poly(siloxane-imide) powder in 15 ml of tetrahydrofuran and add ZnCl 2 20.46 mg (0.00015 mol), stirred at 25 ° C for 3 hours, the reaction solution was concentrated and poured into a mold. After the solvent was evaporated, it was vacuum dried at 80 ° C for 2 hours to obtain a coordinated cross-linked poly (siloxane-imide) thermoplastic elastomer, which can be repeatedly dissolved and hot-pressed.
[0104] The elastomeric material has the following properties: the tensile strength of the material is 18 MPa, the elongation at break is 110%, and the thermoplastic temperature is 116.8°C.
[0105] The difference between this comparative example and Example 1 is that the prepolymerization and chain extension are carried out basically at the same time. Since the formation of amic acid from anhydride and diamine is a reversible reaction, when the prepolymerization and chain extension are carried out simultaneously, after the reaction equilibrium of the polyamic acid is reached, the formed polymer structure may deviate from the expected compound structure, and the aminoalkyl-terminated polysiloxane has a relatively low polarity and is at a disadvantage in the competitive reaction, resulting in a significant decrease in the strength and thermoplastic temperature of the obtained material.
Claims
1. A high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer, characterized in that: The general structure is as follows: Wherein: m, x, s, h, n are all integers greater than or equal to 1; Ar1 and Ar2 are independently selected from C 6-16 Aromatic hydrocarbon groups or C containing S, N, O, F or Cl heteroatoms 6-16 Aromatic hydrocarbon groups; R1, R2, R3, and R4 are independently selected from hydrogen, a linear hydrocarbon group, a branched alkyl group, or a cyclic alkyl group having 1 to 18 carbon atoms and containing S, N, O, or F heteroatoms or not containing the above heteroatoms, a linear or branched unsaturated hydrocarbon group having 2 to 10 carbon atoms and containing one or more unsaturated double bonds and containing S, N, O, or F heteroatoms or not containing the above heteroatoms, and an aromatic hydrocarbon group having 6 to 12 carbon atoms and containing S, N, O, or F heteroatoms or not containing the above heteroatoms; R1, R2, R3, and R4 are the same or different; M is a metal ion.
2. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that: In formula (I), Ar1 and Ar2 are independently selected from R1, R2, R3, R4 are independently selected from hydrogen, methyl, ethyl, propyl, trifluoropropyl, ethyl nitrile, phenyl, vinyl, mercaptomethyl, mercaptopropyl; M is selected from Zn 2+ , Fe 3+ , Cu 2+ 、Co 2+ Sn 2+ or Pb 2+ .
3. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that: In formula (I), 1≤x≤200, 1≤s≤20.
4. The high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 1, characterized in that: The thermoplastic temperature of the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer is 120-155° C., the tensile strength is ≥35 MPa, and the elongation at break is ≥150%.
5. A method for preparing a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to any one of claims 1 to 4, comprising the steps of: (1) in a solvent, an aromatic dianhydride and an aminoalkyl-terminated polysiloxane are reacted to obtain a poly(siloxane-amic acid) prepolymer solution; (2) adding a carboxyl-substituted aromatic diamine to a poly(siloxane-amic acid) prepolymer solution to obtain a poly(siloxane-amic acid) solution through reaction; adding a catalyst to carry out imidization reaction, and then precipitating and drying to obtain a solid polymer poly(siloxane-imide); (3) The solid polymer poly(siloxane-imide) is dissolved in an organic solvent, a metal salt is added, reacted, and then the solvent is removed to obtain a high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer.
6. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that: In step (1), one or more of the following conditions are included: i. The solvent is a mixed solvent of solvent A and solvent B, wherein the volume ratio of solvent A to solvent B is (1-5):(1-5); preferably, solvent A is selected from N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, methyl isobutyl ketone, γ-butyrolactone, dimethyl sulfoxide, acetonitrile, dioxane, xylene or isopropanol; solvent B is selected from tetrahydrofuran, toluene, chloroform, dichloromethane, petroleum ether, n-hexane or ethyl acetate; ii. the volume ratio of the total mass of the aromatic dianhydride and the aminoalkyl-terminated polysiloxane to the solvent is 50 to 200 g / L; iii. The molar ratio of the aromatic dianhydride to the aminoalkyl-terminated polysiloxane is (1-4):1; iv. The reaction temperature is 0 to 80°C, the reaction time is 1 to 24 hours, and the reaction is carried out under stirring and inert gas protection; preferably, the reaction temperature is 20 to 30°C, the reaction time is 6 to 10 hours, and the inert gas is nitrogen or argon; v. The preparation method of poly(siloxane-amic acid) prepolymer solution comprises the steps of: dissolving aromatic dianhydride in solvent A, adding dropwise a mixture of aminoalkyl-terminated polysiloxane and solvent B under stirring, and obtaining poly(siloxane-amic acid) prepolymer solution through reaction after the addition is completed.
7. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that: In step (1), one or more of the following conditions are included: i. Aromatic dianhydride is selected from C 10-20 Aromatic dianhydrides or C containing S, N, O, F or Cl heteroatoms 10-20 Aromatic dianhydride; preferably, the aromatic dianhydride is selected from hexafluoroisopropylphthalic anhydride, 4,4'-oxydiphthalic anhydride or 3,3',4,4'-benzophenonetetracarboxylic dianhydride; ii. The aminoalkyl-terminated polysiloxane is selected from bis(3-aminopropyl)-terminated polydimethylsiloxane, bisaminopropyl poly(methylethyl)siloxane, bisaminopropyl poly(methyltrifluoropropyl)siloxane, bisaminopropyl poly(methylphenyl)siloxane, bisaminoethyl polydimethylsiloxane, bisaminoethyl poly(methylethyl)siloxane, biscyclohexylaminopropyl polydimethylsiloxane, bisaminophenylpropyl polydimethylsiloxane, bisaminoethyl poly(methyltrifluoropropyl)siloxane or bisaminoethyl poly(methylphenyl)siloxane; preferably, the weight average molecular weight range of the aminoalkyl-terminated polysiloxane is 162 to 16000 g / mol, preferably 400 to 1100 g / mol.
8. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that: In step (2), the carboxyl-substituted aromatic diamine is selected from C 7-17 A carboxyl-substituted aromatic diamine; preferably, the carboxyl-substituted aromatic diamine is selected from 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, 2,4-diaminobenzoic acid, 2,6-diaminobenzoic acid or 5,5'-methylenediaminobenzoic acid.
9. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that: In step (2), one or more of the following conditions are included: i. Add the carboxyl-substituted aromatic diamine into the reaction system in 2 to 3 times, with the interval between each addition being 10 to 20 minutes; ii. The molar ratio of the carboxyl-substituted aromatic diamine to the aromatic dianhydride in step (1) is 1-1.1:1; iii. The reaction temperature is 0 to 80°C, the reaction time is 1 to 24 hours, and the reaction is carried out under stirring and inert gas protection; preferably, the reaction temperature is 20 to 30°C, the reaction time is 6 to 10 hours, and the inert gas is nitrogen or argon; iv. The catalyst is selected from organic amines, organic phosphines, pyridines, benzopyridines, amidines or organic guanidine compounds; preferably, the catalyst is selected from one or a combination of two or more of triethylamine, hexamethylenetetramine, pyridine or isoquinoline; v. The molar ratio of the catalyst to the carboxyl-substituted aromatic diamine is 1:(1-2); vi. The imidization reaction temperature is 60 to 200° C., the imidization reaction time is 1 to 24 hours, and the imidization reaction is carried out under stirring conditions and inert gas protection; preferably, the imidization reaction temperature is 170 to 190° C., the imidization reaction time is 6 to 10 hours, and the inert gas is nitrogen or argon; vii. The precipitation is carried out using a mixed solution of anhydrous methanol and water, wherein the volume ratio of anhydrous methanol to water is 1:
1.
10. The method for preparing the high-strength poly(siloxane-imide) high-temperature thermoplastic elastomer according to claim 5, characterized in that: In step (3), one or more of the following conditions are included: i. The organic solvent is selected from one or a combination of two or more of tetrahydrofuran, ethyl acetate, isopropanol, toluene, chloroform, dichloromethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, acetonitrile, dioxane or xylene; ii. The volume ratio of the molar amount of the carboxyl-substituted aromatic diamine in step (2) to the organic solvent in step (3) is 0.1-1 mol / L; iii. The metal salt is selected from one or a combination of two or more of metal halides, metal nitrates, metal sulfates or organic metal salts; preferably, the metal salt is selected from ferric acetylacetonate, zinc acetate, cobalt chloride, copper sulfate, lead nitrate, zinc chloride or stannous isooctanoate; iv. the molar ratio of the metal salt to the carboxyl-substituted aromatic diamine in step (2) is 1:7-20; v. The reaction temperature is 20-50°C, the reaction time is 1-3h, and the reaction is carried out under stirring conditions.
Citation Information
Patent Citations
Process for producing polyimide siloxane solution composition, and polyimide siloxane solution composition
CN102575008A
Soluble poly (siloxane-co-imide) block copolymer film and preparation and application thereof
CN112870998A
Cross-linked polyimide-based composite aerogel and preparation method thereof
CN113831582A
Adhesive polyimide resin and adhesive laminate
CN1406262A
Resin composition and sheet using the same
JP2020084067A
Cited By
Intrinsic porous polyimide film material and preparation method thereof
CN119842076A
High-toughness thermoplastic polyimide elastomer and preparation method thereof
CN120775193A